‘Tidak Menang Tampang Doang’: Kombinasi Outer dan Inner Beauty di Kalangan Mahasiswi - Andi Tri Purnama Sari (ETNOSIA : Jurnal Etnografi Indonesia, 2017)
How women interpret their own body is associated with their social environment since beauty indicators is unique. This article deals with how female student perceive beauty and how this is related to their academic life. To be beautiful is something that is coveted and sought by almost all women, including college female students. For them, campus is not only a place for studying, but also a place for displaying beauty. Beauty is important for female students because it significantly affects one’s self-confidence and provides various advantages, particularly related to administrative and academic affairs. Beauty that is coveted by female students is a combination between outer and inner beauty. While the former is associated with ‘prettiness’ (keindahan) of physical appearance (hair, face, body shape and body skin), the latter is related to ‘attractiveness’ (kemenarikan) of non-physical appearance (intellectual quotient and personality). In the context of academic capability, female students who rely on beauty, but are not smart are considered as students who are ‘menang tampang doang’, not to mention when they haven’t had both. In addition, female students who are not smart, but has good personality will look beautiful. However, those who have the combination of beauty and intelligence are seen as ‘mahasiswi plus-plus’ and are regarded as students who are ‘tidak menang tampang doang’. This underlines the complementarity between inner and outer beauty.